Revisiting the God/World Difference. (27th October 2017) - Holmes, Christopher R.J.
Abstract: On what basis do we distinguish God from the world? I argue that the doctrine of creation, more specifically the analogical notion of causa, supplies a salutary foundation. My conversation partners are Karl Barth and Thomas Aquinas. I take up the former's five conditions for a right theological use of causa, demonstrating that despite his basic misreading of Thomas, both theologians share some basic convictions regarding God's independence. I argue, moreover, that Thomas provides a more theologically satisfying anchor for what distinguishes God from what is not God. I conclude by reflecting on the importance of experience in articulating the distinction.